Organ‐Restricted Vascular Delivery: Organ‐Restricted Vascular Delivery of Nanoparticles for Lung Cancer Therapy (Adv. Therap. 7/2020). Issue 7 (10th July 2020) - Bölükbas, Deniz A.; Datz, Stefan; Meyer‐Schwickerath, Charlotte; Morrone, Carmela; Doryab, Ali; Gößl, Dorothee; Vreka, Malamati; Yang, Lin; Argyo, Christian; van Rijt, Sabine H.; Lindner, Michael; Eickelberg, Oliver; et al.
Abstract : Despite their immense potential, clinical translation of nanomedicines is hampered by physicochemical and biological barriers impairing cell‐specific targeting especially in solid tumors. In article number 2000017 Darcy E. Wagner, Silke Meiners and co‐workers report a novel approach using organ‐restricted vascular delivery (ORVD) with direct administration and recirculation of nanoparticles to enhance nanoparticle uptake in lung tumors. ORVD opens up new avenues for optimized nanotherapies.